PRODUCTION OF ENZYMES IN PREDOMINANT THERMOPHILIC FUNGI AVAILABLE FROM ORGANIC SUBSTRATES: - (International Journal of Scientific Research and Management (IJSRM), 2021)
Present investigation describes that the study site comes under Aurangabad Division Maharashtra and it falls in Deccan Plateau Zone of India. It was collected different types of organic substrates viz. vermiompost, poultary manure, baggase, farm yard manure (FYM), soil, Ash etc. Isolated thermophilic predominant fungi thermophilic fungi viz.Aspergillus niger, Mucor mucedo,Humicola insolens,Trichoderma harzianum,T. viride,Penicillium duponti,Fusarium oxysporun and Chaetomium thermophilum were carried out for the production of enzymes. Isolated predominant thermophilic fungi were evaluated on different types of enzymes. Among tested thermophilic fungi, the highest ativity was observed in C. thermophilium (20mm) followed by T. harzianum (19.50mm) In lipase, M. mucedo (15.40mm) was found maximum followed by F. oxysporun. Cellulase activity was found highest in A. nige (25mm) followed by others. In case of xylanase, catalase, peroxidase and esterase activities were found maximum, minimum and medium even negative in some fungi. Maximum pectinase activity was detected from H. insolens (52.26 @ 0 min) and (74.25 @ 10 min) and in case of M. mucedo, F. oxysporun and C. thermophilium was found most extreme while least in A. niger (30.12) and P. duponti (33.47) @ 0 minute. Key words: Organic Substrates, Thermophilic Fungi, Enzymes